ADAPTATION OF MSME BUSINESS ACTORS TO SHARIA DIGITAL FINANCE: Case Study On “Cuan Store” Business Actors In Samarinda City - Ma’wa, Zahiroh Jannatul; Septianingtias, Septianingtias; Mulia, Farra Dwi (Institut Agama Islam Negeri Kerinci, 2024)
Purpose: The purpose of this study is to identify how micro, small and medium enterprises